Spinal PAR2 Activation Contributes to Hypersensitivity Induced by Peripheral Inflammation in Rats - Mrozkova, Petra; Spicarova, Diana; Palecek, Jiri (International journal of molecular sciences, 2021)
The mechanisms of inflammatory pain need to be identified in order to find new superior treatments. Protease-activated receptors 2 (PAR2) and transient receptor potential vanilloid 1 (TRPV1) are highly co-expressed in dorsal root ganglion neurons and implicated in pain development. Here, we examined the role of spinal PAR2 in hyperalgesia and the modulation of synaptic transmission in carrageenan-induced peripheral inflammation, using intrathecal (i.t.) treatment in the behavioral experiments and recordings of spontaneous, miniature and dorsal root stimulation-evoked excitatory postsynaptic currents (sEPSCs, mEPSCs and eEPSCs) in spinal cord slices. Intrathecal PAR2-activating peptide (AP) administration aggravated the carrageenan-induced thermal hyperalgesia, and this was prevented by a TRPV1 antagonist (SB 366791) and staurosporine i.t. pretreatment. Additionally, the frequency of the mEPSC and sEPSC and the amplitude of the eEPSC recorded from the superficial dorsal horn neurons were enhanced after acute PAR2 AP application, while prevented with SB 366791 or staurosporine pretreatment. PAR2 antagonist application reduced the thermal hyperalgesia and decreased the frequency of mEPSC and sEPSC and the amplitude of eEPSC. Our findings highlight the contribution of spinal PAR2 activation to carrageenan-induced hyperalgesia and the importance of dorsal horn PAR2 and TRPV1 receptor interactions in the modulation of nociceptive synaptic transmission.
Keywords: miniaturní postsynaptické potenciály; Anilides; TRPV Cation Channels; TRPV1; thermal hyperalgesia; Male; peripheral inflammation; Rats, Wistar; Carrageenan; staurosporin; Cinnamates; Hyperalgesia; inflammatory pain; excitační postsynaptické potenciály; PAR2; synaptic transmission; mužské pohlaví; potkani Wistar; karagenan; nocicepce; receptor PAR-2; krysa rodu Rattus; Animals; superficial dorsal horn; nociception; anilidy; Miniature Postsynaptic Potentials; zvířata; buňky zadních rohů míšních; Rats; cinnamáty; Posterior Horn Cells; Staurosporine; Nociception; kationtové kanály TRPV; spinal cord; hyperalgezie; Excitatory Postsynaptic Potentials; Receptor, PAR-2